Etyka a globalny ład gospodarczy - Przybyciński, Tomasz (Annales. Etyka w Życiu Gospodarczym, 2013)
It is a great developmental challenge to create the global economic order. Economic and ethical values must be taken into account to manage this task, otherwise the prosperity of the global economy is in danger.